The Impact of Consumer Purchase Intention and Halal Brand Equity on Halal-Labeled Instant Noodle Products in Indonesia - Ceini Anggar Kusuma; Dudi Anandya (Program MM Universitas Surabaya, 2023)
Purpose: This research aims to examine the impact of consumer purchase intention and halal brand equity from a halal perspective, namely halal brand image, halal brand perceived quality, halal brand satisfaction, halal brand trust, and halal brand loyalty. Method: This research employs an online questionnaire to collect data from 210 respondents aged 17 and above who have experience consuming halal-labeled instant noodles in Indonesia. Based on the research objective, it falls under basic research. Based on the research type, it falls under causal research. Based on the research approach, this research is classified as quantitative research. Furthermore, this research aims to elaborate on the relationships between halal brand image, halal brand perceived quality, halal brand satisfaction, halal brand trust, halal brand loyalty, purchase intention, and halal brand equity. The theoretical model with hypothesized relationships was developed and tested using the structural equation modeling procedure in SPSS AMOS. Result: The findings of this research indicate that halal brand image has a significant and positive influence on halal brand perceived quality, halal brand satisfaction, halal brand trust, halal brand loyalty, and purchase intention. Similarly, halal brand perceived quality, halal brand satisfaction, halal brand trust, and halal brand loyalty have a significant and positive influence on purchase intention. Furthermore, halal brand satisfaction significantly and positively influences halal brand equity, but the relationship between halal brand trust and halal brand equity could not be established.